2017
DOI: 10.5539/ies.v10n11p47
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of EFL Students Using the Systemic Functional Linguistics Method

Abstract: This study examined the progress of English as a foreign language (EFL) writers using the instructional framework of systemic functional linguistics (SFL) and the communities of practice (CoPs) model. The study participants comprised 11 first-year undergraduate students in Japan with intermediate-level English proficiency who were exposed to SFL in a single EFL classroom (CoP). The participants' genre understanding and meaning-making decisions when writing discussion essays were studied over two semester-long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…How do understandings of the basic structures and lexicogrammatical features of texts differ between novice and experienced learners? The pre-and post-survey results of the present study indicated that the learners' understanding of the structure of the discussion genre improved, regardless of whether the learner was a novice or an experienced student of genre-based writing, which is consistent with the findings of Nagao (2017). In addition, the results of our analysis of the learners' preinstruction/noninstructional and post-instruction essays showed that their structural understanding had also improved, although in this regard there were differences between novice and experienced learners.…”
Section: Discussionsupporting
confidence: 88%
“…How do understandings of the basic structures and lexicogrammatical features of texts differ between novice and experienced learners? The pre-and post-survey results of the present study indicated that the learners' understanding of the structure of the discussion genre improved, regardless of whether the learner was a novice or an experienced student of genre-based writing, which is consistent with the findings of Nagao (2017). In addition, the results of our analysis of the learners' preinstruction/noninstructional and post-instruction essays showed that their structural understanding had also improved, although in this regard there were differences between novice and experienced learners.…”
Section: Discussionsupporting
confidence: 88%
“…The questions that comprised this peer genre analysis task, which are listed in Table 2, were especially focused on modal verbs and the features of the generic structures. The task involved students reflecting on their peers' writing in order to increase their own genre awareness (Yasuda, 2011;Nagao, 2017). In Task 2, the students shared and discussed their genre analyses with one another, as a group activity, trying to discern similarities and differences.…”
Section: The Sfl-oriented Genre-based Pedagogical Approach To Writinmentioning
confidence: 99%
“…Studies have shown that EFL students face significant challenges in developing their academic literacy skills ( Correa, 2010 ; Nagao, 2017 ; Singh, 2019 ; Zhang W. J., 2020 ; Rodas and Colombo, 2021 ). Among them, one major challenge is the lack of proficiency in English, which hinders their ability to read and write academic texts in the English language.…”
Section: Introductionmentioning
confidence: 99%